(3egPH GdhUhd Edi Yde GdCUhds - (3eMeO egOj Hf GdMSf Hf CMeO GdMSjfj GdbRhjfj GdfLaj,J (B1300 (3g` s; (3GdHgHgGfj , eMeO HGbQ Hf eMeO Gced,J (B1206 (3g` s
(3ChdgG (B:s
(3HYO ajbhd GdQGLi Yah QHg GdZfi eMeO Hf GdMSf s
(3BNQgG (B:s
(3HGdcJGHI hGdMK YdjgG dHfjc adh s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3JgPjHs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3CUhd Gdabgs